2022
DOI: 10.1080/21655979.2021.2018386
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: N(6)-adenosine-methyltransferase-14 promotes glioma tumorigenesis by repressing argininosuccinate synthase 1 expression in an m6A-dependent manner

Abstract: Glioma is one of the leading causes of tumor-related deaths worldwide, but its potential mechanism remains unclear. This study aimed to explore the biological role and potential mechanism of argininosuccinate synthase 1 (ASS1) in glioma. The relative expression levels of ASS1 in glioma specimens and cell lines were calculated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blotting. The biological functions of ASS1 were demonstrated using the 5-ethynyl-2ʹ-deoxyuridine (EdU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…An increasing number of studies have focused on the role of RNA m 6 A methylation in the development of various neurological diseases, such as Parkinson’s disease [ 23 ], Alzheimer’s disease [ 24 , 25 ], multiple sclerosis [ 26 ], tumours [ 27 , 28 , 29 ], epilepsy [ 30 ], and neuropsychiatric disorders [ 31 ]. However, to date, there is limited research focusing on the role of RNA m 6 A methylation in TBI and BGA.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have focused on the role of RNA m 6 A methylation in the development of various neurological diseases, such as Parkinson’s disease [ 23 ], Alzheimer’s disease [ 24 , 25 ], multiple sclerosis [ 26 ], tumours [ 27 , 28 , 29 ], epilepsy [ 30 ], and neuropsychiatric disorders [ 31 ]. However, to date, there is limited research focusing on the role of RNA m 6 A methylation in TBI and BGA.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed the unique role of m6A RNA methylation in the genesis and development of cancer including glioma. A series of studies using the knockdown model of METTL3 and METTL14 observed a reduction of m6A extent accompanied by upregulation of oncogenes and downregulation of tumor suppressors [20,21] . On the contrary, overexpression of METTL3 leads to decreased proliferation and migration of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Methyltransferase 14 (METTL14), a RNA N6-adenosine methyltransferase, participates in tumor development via modulating RNA function (Chen et al, 2020). ASS1 is a target of METTL14mediated N6-methyladenosine modification (Miao et al, 2022). Specifically, METTL14 upregulation increases mRNA m6A modification of ASS1 and suppresses ASS1 transcriptional expression.…”
Section: Ass1 Regulation and Signaling Networkmentioning
confidence: 99%